Heart rate variability during speed-strength load of athletes after hypoventilation training - Yu. E. Vaguine; S. Ya. Klassina; N. A. Fudin (National Electronic Information Consortium (NEICON), 2022)
Objective: to study the variability of the heart rate of athletes during hypoventilation training, which provides an increase in the result of speed-strength load.Materials and methods: Athletes performed speed-strength load with their hands on a training apparatus against the background of maximum voluntary breath holding before and after hypoventilation training. The duration of breath holding, the number of power movements, parameters of heart rate variability and electromyography were measured.Results: After hypoventilation training of athletes at rest, parasympathetic influences on the heart rate increased, which led to an increase in the total power of the heart rate spectrum from 3201 ± 520 to 4047 ± 585 ms2, the power of the low frequency of the heart rate spectrum from 1458 ± 216 to 2055 ± 392 ms2 and the standard deviation of the duration of adjacent cardiac cycles from 45 ± 5 to 52 ± 4 ms. Sympathetic influences increased during exercise against the background of maximum voluntary breath holding. The longer maximum voluntary breath holding was, the more power movements the athletes performed.Conclusion: Hypoventilation training changed the vagosympathetic balance of the athletes' body, increasing their performance and hypoxic resistance.